Harnessing hesperidin for brain metabolism: epigenetic signatures, cellular homeostasis, synaptic function, and neuroprotection in age-related diseases and neurodegenerative diseases - Zhao, Wei; Hong, Wenwu; Cao, Yingying (Frontiers in Nutrition, 2025)
Age-associated neurodegenerative disorders constitute a considerable global health concern, distinguished by a progressive deterioration in cognitive function, synaptic impairment, and disrupted cellular homeostasis. Recent research has identified hesperidin (HSP), a bioactive flavonoid predominantly present in citrus fruits, as a potentially valuable neurotherapeutic compound due to its diverse molecular mechanisms of action. This review aims to consolidate existing literature regarding HSP’s ability to influence epigenetic modifications, augment synaptic plasticity, and restore cellular equilibrium in the aging central nervous system. We investigate the manner in which HSP affects critical epigenetic markers, such as DNA methylation and histone modifications. Therefore it modulates gene expression essential for neuroprotection and lifespan extension. Furthermore, we examine the role of HSP in the preservation of synaptic integrity and neurotransmission, which are crucial for cognitive resilience in the face of age-related deterioration. The review further clarifies the antioxidant and anti-inflammatory properties of HSP, which together promote neuronal viability and alleviate neurodegenerative pathology. By synthesizing mechanistic insights and preclinical evidence, this article underscores the potential of HSP as a natural compound for both the prevention and adjunctive treatment of neurodegenerative disorders, thereby advocating for translational research aimed at realizing its full therapeutic efficacy.